LABORATORY AND BIOCHEMICAL PARAMETERS IN PATIENTS WITH HEPATITIS B, C AND C+B WITHIN FIVE YEARS OF ANTIVIRAL THERAPY - Gavrilyuk, A.O. (World of Medicine and Biology, 2015)
The analysis of antiviral therapy of chronic hepatitis B and C showed that within 5 years of observation in the vast majority of patients experienced a significant decrease in the severity necrotic and inflammatory changes in the liver and liver fibrosis stabilization. Stabilization of inflammatory and fibrotic changes in the liver observed in some patients who have failed to achieve complete elimination of the virus.